2010
DOI: 10.4239/wjd.v1.i4.116
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of lipid-lowering drugs on circulating adipokines

Abstract: The cardioprotective effects of lipid-lowering drugs have been primarily attributed to their effects on blood lipid metabolism. However, emerging evidence indicates that lipid-lowering drugs also modulate the synthesis and secretion of adipose tissue-secreted proteins referred to as adipokines. Adipokines influence energy homeostasis and metabolism and have also been shown to modulate the vascular inflammatory cascade. The purpose of this review will be to examine the reported effects of commonly used lipid-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 131 publications
0
24
0
2
Order By: Relevance
“…In an animal model of T2DM, atorvastatin exerts significant lipid and glucose lowering effects and decreased plasma insulin levels and insulin resistance index. Although the primary goal of atorvastatin is to improve blood lipid and lipoprotein characteristics, beneficial effects on energy metabolism and cardiovascular function such as improved endothelial function, reduced oxidative stress, decreased platelet adhesion and increased atherosclerotic plaque stability may help to explain at least part of the cardioprotective benefits of these agents [30] . The results of the present work were also supported by Harp [31] who reported that the use of the pancreatic lipase inhibitor orlistat helps to lose weight due to decrease the absorption of dietary lipids.…”
Section: Resultsmentioning
confidence: 99%
“…In an animal model of T2DM, atorvastatin exerts significant lipid and glucose lowering effects and decreased plasma insulin levels and insulin resistance index. Although the primary goal of atorvastatin is to improve blood lipid and lipoprotein characteristics, beneficial effects on energy metabolism and cardiovascular function such as improved endothelial function, reduced oxidative stress, decreased platelet adhesion and increased atherosclerotic plaque stability may help to explain at least part of the cardioprotective benefits of these agents [30] . The results of the present work were also supported by Harp [31] who reported that the use of the pancreatic lipase inhibitor orlistat helps to lose weight due to decrease the absorption of dietary lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Для фармакотерапии ДЛП применяются статины, фи-браты, секвестранты желчных кислот, никотиновая кисло-та и ее производные, препараты длинноцепочечных -3 и -6 ПНЖК или, в качестве альтернативы, их комбинация с ингибиторами абсорбции холестерина [28].…”
Section: лечение дислипопротеинемииunclassified
“…The majority of the available studies were mostly carried out on experimental animals and provided inconsistent findings [12]. Therefore, the aim of this trial was to determine the effect of n-3 PUFAs on plasma resistin, MCP-1, and the adiponectin-resistin index.…”
Section: Beneficial Effects Of N-3 Fatty Acids Onmentioning
confidence: 99%